"Blessing" Waste Bank Program in Sidoarjo Regency: Program Bank Sampah "Berkah" di Kabupaten Sidoarjo - Arum Ridho Intiaswilujeng; Isna Fitria Agustina (Academia Open, 2022)
The Blessing Waste Bank Program in Kepuhkemiri Village aims not only to protect the environment, but also to reduce the amount of waste in the area. In addition, the waste bank program is believed to be able to support the community's economy by exchanging waste for rupiah. This study aims to provide insight into how the Blessing Waste Bank program operates every year. The use of a qualitative approach to research methods. Methods of collecting data through interviews, field observations, and documentation. It collects two types of data, primary data and secondary data. Researchers used data analysis methods Sugiyono (2010): data collection, data reduction, data presentation, and reasoning. From the results of this study, the Blessing Waste Bank program has been running according to predetermined indicators. Highlights: The Blessing Waste Bank Program in Kepuhkemiri Village aims to protect the environment and reduce waste while supporting the local economy. This study utilizes a qualitative research approach and collects data through interviews, field observations, and documentation. The results indicate that the Blessing Waste Bank program operates successfully based on predetermined indicators, highlighting its effectiveness in waste management and community engagement. Keywords: Blessing Waste Bank Program, Environment protection, Waste management, Community economy, Qualitative research.